Asynchronous geographic logical volume mirroring best practices for cloud deployment - Quintero, Dino; Shankar, Ravi A.; Steel, Antony (IBM redbooks., 2022)
This IBM® Redpaper™ publication describes IBM Geographic Logical Volume Manager (GLVM) for data mirroring in cloud deployments. Asynchronous GLVM provides IBM AIX® based mirroring of data across distance over networks. It is highly recommended that Asynchronous GLVM be deployed with PowerHA SystemMirror for AIX Enterprise Edition. PowerHA® SystemMirror® provides robust workload stack HA management, handles many errors in the environment, and helps recover Asynchronous GLVM better. PowerHA SystemMirror also provides interfaces for easy setup of Asynchronous GLVM and disk management. This IBM Redpaper publication provides guidelines in relation to GLVM deployments for private or public clouds. This publication is intended to help with the requirements to configure and implement GLVM for cloud configurations. This paper addresses topics for IT architects, IT specialists, sellers and anyone who wants to implement and manage high availability (HA) and Disaster Recovery (DR) in the cloud. The publication also provides documentation to transfer the how-to skills to the technical teams, and solution guidance to the sales team. This paper compliments the documentation that is available at the IBM Documentation web page and aligns with the educational materials that are provided by IBM Systems Technical Education.